Nutritional Value and Therapeutic Benefits of Dragon Fruit: A Comprehensive Review with Implications for Establishing Australian Industry Standards - Si-Yuan Chen; Cheng-Yuan Xu; Muhammad Sohail Mazhar; Mani Naiker (Molecules)
Dragon fruit, which is native to northern South America and Mexico, has become a significant crop in tropical and subtropical regions worldwide, including Vietnam, China, and Australia. The fruit (Hylocereus spp.) is rich in various bioactive phytochemical compounds, including phenolic acids, flavonoids, and pigments such as betalains and anthocyanins, which contribute to its antioxidant, anti-inflammatory, and anti-microbial properties. This comprehensive review introduces the origin, classification, and global production of dragon fruit, with a particular focus on its bioactive phytochemicals and therapeutic potential. Additionally, it critically evaluates the current industry standards for fresh dragon fruit production across key producing countries. While these standards primarily focus on quality, classification, and grading criteria, they lack focus on parameters related to the fruit’s bioactive content. The absence of established quality standards for fresh produce in the Australian dragon fruit industry presents a unique opportunity to develop guidelines that align with both international benchmarks and the therapeutic potential of the fruit. By addressing this gap, this review can potentially help Australia to position its dragon fruit industry to achieve greater consistency, competitiveness, and consumer appeal. As the demand for functional foods continues to rise, aligning Australian production practices with global standards becomes critical to meeting domestic market expectations. This review provides a comprehensive understanding of dragon fruit’s nutritional and therapeutic significance and highlights its potential role in establishing a robust standard for the Australian dragon fruit industry. A review of global industry standards reveled that Australian standard could incorporate classifications of dragon fruits, including external factors like appearance, size, and defect tolerance. Future research is needed to prioritize understanding of the impact of cultivation practices and environmental factors on the bioactive composition of dragon fruit, enabling the development of best practices for growers. Additionally, further studies are needed to evaluate the therapeutic effects of these bioactive properties through clinical trials, particularly their potential in preventing chronic diseases. The advancement of analytical methods for quantifying bioactive compounds will provide deeper insights into their health benefits and support the establishment of bioactive-oriented industry standards. Moreover, investigations of post-harvest handling and processing techniques could optimize the preservation of these valuable compounds, enhancing dragon fruit’s role as a functional food.